Physical activity and nutrition behaviour outcomes of a cluster-randomized controlled trial for adults with metabolic syndrome in Vietnam. Issue 1 (December 2017) - Tran, Van; Lee, Andy; Jancey, Jonine; James, Anthony; Howat, Peter; Mai, Le
Abstract Background Metabolic syndrome is prevalent among Vietnamese adults, especially those aged 50–65 years. This study evaluated the effectiveness of a 6 month community-based lifestyle intervention to increase physical activity levels and improve dietary behaviours for adults with metabolic syndrome in Vietnam. Methods Ten communes, involving participants aged 50–65 years with metabolic syndrome, were recruited from Hanam province in northern Vietnam. The communes were randomly allocated to either the intervention (five communes, n  = 214) or the control group (five communes, n  = 203). Intervention group participants received a health promotion package, consisting of an information booklet, education sessions, a walking group, and a resistance band. Control group participants received one session of standard advice during the 6 month period. Data were collected at baseline and after the intervention to evaluate programme effectiveness. The International Physical Activity Questionnaire – Short Form and a modified STEPS questionnaire were used to assess physical activity and dietary behaviours, respectively, in both groups. Pedometers were worn by the intervention participants only for 7 consecutive days at baseline and post-intervention testing. To accommodate the repeated measures and the clustering of individuals within communes, multilevel mixed regression models with random effects were fitted to determine the impacts of intervention on changes in outcome variables over time and between groups. Results With a retention rate of 80.8%, the final sample comprised 175 intervention and 162 control participants. After controlling for demographic and other confounding factors, the intervention participants showed significant increases in moderate intensity activity (P  = 0.018), walking (P  < 0.001) and total physical activity (P  = 0.001), as well as a decrease in mean sitting time (P  < 0.001), relative to their control counterparts. Significant improvements in dietary behaviours were also observed, particularly reductions in intake of animal internal organs (P  = 0.001) and in using cooking oil for daily meal preparation (P  = 0.001). Conclusions The prescribed community-based physical activity and nutrition intervention programme successfully improved physical activity and dietary behaviours for adults with metabolic syndrome in Vietnam. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12614000811606 . Registered on 31 July 2014